Building a training program based on the skills of conscious discipline in the performance of applied students in the Arabic language departments in the faculties of education (Journal of the College of Basic Education, 2023)
Building an experimental program based on the skills of conscious discipline in the performance of students applied at departments of Arabic language, colleges of educationTo achieve this, the researcher followed the descriptive approach in the procedures of building the training program through three main stages: planning, implementation and evaluation.The researcher specified the justifications for building the training program, its philosophy and intellectual premises, its objectives, both public and private. The researcher, moreover, organized the training content and identified training methods and means consistent with the objectives of the training programThe researcher used an experimental design with partial control and a post-test. The researcher prepared the research tool, which is the observation card form, which consisted of (40) items and its validity and reliability were verifiedBased on the foregoing, the researcher concluded that the training program proved to be effective in developing the teaching performance of students applied.key words : Education, the Arabic language, methods of teaching the Arabic language, training, training programs, applied studentsNote: the research is derived from a PhD thesis